Implementasi Automatic Uplink Power Control (AUPC) Pada VSAT Single Channel Per Carrier (SCPC) - Taufik Rahman; Fatwa Aulia Rahman (P3M Politeknik Negeri Bengkalis, 2020)
The cable network is not suitable for connecting geographically distant communication systems such as Indonesia due to the low efficiency of the installation process, which requires large capital. It needs alternative technology, such as Very Small Aperture Terminal (VSAT) but it is vulnerable to interference and equipment weaknesses that will reduce performance. Weather in Indonesia is erratic, sometimes suddenly raining makesVSAT communication network vulnerable to interference, because it adjusts transmit power manually. Especially forVSAT network of PT. Megah Surya Pertiwi, PIC inlocation does not understand VSAT. Based onresults of analysis and testing, there was a decrease in ping quality, Eb/No, C/N when it rained. Need to adjust transmit power so that quality returns to normal with weather at location. Prior toimplementation of Automatic Uplink Power Control, modem at Graha HUB independently defaulted power at 0dB and at Kawasi site at 2dB, when it rained and power was not increasedlink became unstable there was a Request time out and intermittent with occasional ping>1000ms,current C/N value weather is good at a value of 20.34dB while when it rains at 17.42dB and Eb / No value is unstable. After AUPC power transmits automatically adjusts. Ping value becomes more stable, ping on VSAT can be good if delay value is 500-800ms, with a maximum delay of 770ms toIP Modem monitoring site and 789ms to IP Lan PT. MSP. C/N value obtained is 21.09dB in accordance with ideal C/N range for VSAT networks. Eb/No value is stable according to target, namely 10 dB on the HUB modem and 9 db onmonitoring site modem. When modem detects a decreasing or increasing Eb/No value,system automatically adjusts transmit power so that the Eb/No value matching target.